Tinjauan Literatur Terkini: Peranan Konsumsi Teh terhadap Penyakit Hipertensi: Recent Literature Review: The Effects of Tea Consumption on Hypertension - Balatif, Ridwan; Lubis, Nenni Dwi Aprianti (Universitas Airlangga, 2024)
Background: In Indonesia, the prevalence of hypertension was found to increase from 25.8% (2013) to 34.1% (2018). In additon, patients with this medical condition are generally required to adhere to lifelong anti-hypertensive drugs for blood pressure control. However, recent studies have suggested the use of tea containing active compounds Epigallocatechin-3-gallate (EGCG), which can lower blood pressure. Objectives: This study aimed to provide an overview of active compounds in tea with the potential to lower blood pressure. Methods: The data used were obtained from sources related to randomized controlled clinical trials searched through the Pubmed page in the 2017-2022 period, with various keywords such as tea, blood pressure, and hypertension. Discussions: Out of 35 studies reviewed, a total of 9 were obtained from the literature search. The results showed that EGCG in capsule form with a dose range of 75-300 mg could reduce blood pressure significantly, as observed in studies with capsules containing anthocyanins and polyphenols. Although 4 studies used tea beverages as intervention materials, there was no significant decrease in blood pressure. Furthermore, 2 studies showed a significant variation due to differences in the levels of active compounds and the presence of caffeine in tea, which affected blood pressure measurements. Conclusions: The use of active compounds in tea, particularly EGCG, in recent clinical trials on blood pressure regulation has shown a significant reduction in hypertension. Therefore, exploiting the potential of EGCG in a larger sample size could serve as a promising avenue for future studies.